Clima laboral de la empresa de servicios ocasionales j&arias de la ciudad de Babahoyo, periodo 2022. - Navarrete Sánchez Fabiola Maoli (2023)
Through the realization of this case study, focusing on the work environment, which allowed us to have an object of study focusing on analyzing the factors that influence the work environment of the J&ARIAS Occasional Services company, through the use of research tools, for the improvement of the organizational environment, leading to the fulfillment of that objectivity, as well as the identification of various aspects that arise in the work environment, considering as a scientific basis the use of information collected in texts, articles and investigative journals as well as university repositories. Therefore, this type of case study allowed, through the use of surveys that were applied to the company's collaborators, to identify the behaviors that are developed during the execution of tasks in the establishment, with the purpose of knowing the perspective more detailed information about the work environment and business policies. Which leads to determining that through the research tools it is possible to detect the non-conformities or problems that arise in each process executed internally, therefore, the use of the information would be proposed to the Occasional Services company J&ARIAS. which rests on this work, with the purpose of having supported and verified bases around the different procedures that are carried out in your organization, based on what was analyzed for the 2022 period.